IMPLEMENTASI BIMBINGAN KARIR DALAM MENGEMBANGKAN PERENCANAAN KARIR SISWA DI SMA MA’ARIF BANDUNG - Az-zuhri, Dhilla Nuraeni; Risma, Anisa; Ratnawulan, Teti; Asrofi, Imam (Jurnal Manajemen Pendidikan, 2025)
The implementation of career guidance can steer students' career planning. Career planning among grade XII high school students is not yet mature. This study aims to analyze the implementation of career guidance in developing career planning for high school students at SMA Ma’arif Bandung. Employing a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. Findings indicate that the program effectively enhances students’ understanding of their potential, career opportunities, and decision-making skills. Prior to guidance, 70-85% of students were confused and lacked knowledge about the world of work, but post-guidance, 80-90% could formulate clear career goals and concrete steps, with an average improvement of 50-60% in goal clarity, knowledge, and confidence. Supporting factors include principal support and external collaborations, while challenges encompass limited time, resources, and parental pressure. Recommendations include increasing session frequency, counselor training, and technology utilization. This study underscores the importance of structured career guidance in preparing students for post-high school transitions.